The response of debtors to rate changes - Andreas Fuster; Virginia Gianinazzi; Andreas Hackethal; Philip Schnorpfeil; Michael Weber (Goethe University Frankfurt, Center for Financial Studies (CFS), 2026)
How borrowers respond to future changes in the interest rate on their debt matters for the transmission of monetary policy and for household financial stability. Combining bank data, a letter RCT, and a survey, we study this question in the context of the German mortgage market, where since 2022 borrowers have faced high interest rates when their rate fixation period ends. We find that borrower actions substantially reduce the impact of higher rates on monthly payments. Survey responses corroborate high informedness and a strong propensity to prepare for rate changes. The letter intervention does not affect rate beliefs but increases awareness of available options and refinancing among borrowers close to expiration of their rate fixation.
Keywords: 330; Hypothek; Hypothekenzins; Wirkungsanalyse; Private Verschuldung; Konsumentenverhalten; Geldpolitische Transmission; Schätzung; Deutschland